AmNet. Issue 2 (6th April 2020) - Harper, Timothy; Norelli, Barbara; Brandston, Melanie; Taber, Mary
Abstract : Purpose: Micro organizational behavior – an individual level of analysis (i.e. motivation, personality, attitudes, learning, etc.). Meso organizational behavior – team/group level of analysis (i.e. communication, team dynamics, power, politics, etc.). Macro organizational behavior – an organizational level of analysis (i.e. strategy, structure, culture, control, etc.). Marketplace or external environment (PESTEL analysis). Research methodology: The research was conducted by a consultant in the role of a participant-observer. Case overview/synopsis: The focus of the case is a disguised nonprofit organization, the American-Netherlands Foundation (AmNet), based in Chicago. The organization faced leadership and organizational challenges related to conflicting strategic and operational priorities among the board of trustees, the president and staff. An unexpected contribution of $750, 000 increased the salience of these differences. The case provides students an excellent opportunity to apply their analytical skills and knowledge gained in a management and business course. Complexity academic level: Organizational behavior; organizational design; organizational development; and organizational theory. Levels – upper-level undergraduate through first-year MBA students.